Requirements for educational transformation to teach art education courses in light of the knowledge economy (Journal of the College of Basic Education, 2024)
The current research aims to: Disclosure of the requirements of the educational transformation of teaching art education courses towards the knowledge economy, at the College of Basic Education - Al-Mustansiriya University, for the academic year 2020-2021, and the researcher adopted the descriptive approach in building a standards form that includes the requirements of educational transformation in the light of the knowledge economy, which can be employed for the purpose of teaching art education courses, and for this purpose, the researcher followed the following steps in preparing them:Access to educational literature and its relationship to the knowledge economy.The researcher relied on the division of domains.